Intelligence quotient (IQ) outcome in children with early-treated congenital hypothyroidism: a systematic review and meta-analysis - Whyra Pratama Said; Karina Sugih Arto; Winra Pratita; Sufitni Sufitni (Indonesian Pediatric Society, 2023)
Background Congenital hypothyroidism (CH) is the most common congenital endocrine disorder in childhood and is one of the most preventable causes of intellectual disability (ID). Late initiation of thyroid hormone substitution therapy has a negative impact on intellectual abilities in CH patients. Objective To compare Intelligence Quotient (IQ) between children with CH who underwent early treatment among the children without CH. Methods We performed online literature searches of ScienceDirect, Pubmed, Cochrane Library, and Google Scholar. We included clinical studies that examined IQ scores in patients with early-treated CH and without CH. Review Manager 5.4 was used to perform the meta-analysis. Results Twelve studies comparing pediatric patients with and without CH were included in this meta-analysis, for a total of 808 patients. Based on data analysis, IQ levels of verbal IQ [mean difference (MD) -9.05; (95%CI -14.51 to -3.59); (P<0.00001)], performance IQ [MD -11.70; (95%CI -17.41 to -5.99); (P<0.00001)], and total IQ [MD -10.78; (95%CI -14.03 to -7.54); (P<0.00001)]. While verbal, performance, total, of the early-treated CH group were within the normal range, they were each significantly lower than those in the non-CH group. Conclusion This meta-analysis reveals that IQ scores in early-treated CH subjects were within normal limits, but significantly lower than that of normal controls.